A dual laser composite forming method
Patent Information
- Application Number
- CN202611271118.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-30
AI Technical Summary
若为实现半熔融态冲击强化而使超快激光与成形激光紧密跟随,则冲击波冲开粉末后会导致后续成形激光照射区域出现粉末缺失,使得成形激光无粉可熔,无法完成正常成形
本发明通过增加烧结激光束,在成形激光作用于预成形区域之前,预先对松散粉末进行非熔化状态下的烧结处理,使粉末颗粒之间产生烧结颈结合力,从而使粉末由松散状态转变为具有一定抗冲击能力的烧结态。该烧结颈结合力被设计为大于冲击强化激光束冲击波对粉末的驱散力,因此当后续冲击强化激光束产生的冲击波作用于已烧结粉末时,粉末不会被冲击波冲开,避免了现有技术中因粉末被冲开导致成形激光无粉可熔的问题。冲击强化激光束能够在熔池处于半熔融态时对材料实施冲击强化,在半熔融状态下材料的塑性较好、变形抗力较低,冲击波能够有效作用于材料内部,消除孔隙和裂纹等缺陷并细化晶粒,从而实现边成形边强化的连续加工。烧结激光对粉末的预热作用使粉末升温过程由极快速升温转变为梯度式升温,降低了材料中热应力的累积;同时烧结激光对上一成形层也具有预热作用,可缓解上一成形层因快速冷却导致的应力集中,使整个成形及应力调控过程形成闭环,减少了后处理工序。
Smart Images

Figure CN123000010A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of laser additive manufacturing technology, specifically relating to a dual-laser composite forming method. Background Technology
[0002] Selective Laser Melting (SLM) is one of the most promising technologies in additive manufacturing. This technology uses a high-energy-density laser beam to melt metal powder layer by layer, enabling the integrated forming of complex structural parts. The cooling rate of the molten pool during SLM forming can reach 10... 3 K / s to 10 8 With a melting rate of K / s, the forming parts inevitably contain metallurgical defects such as pores and cracks, which severely restrict the mechanical properties and reliability of the forming parts.
[0003] To address these issues, some scholars have proposed introducing ultrafast lasers into the SLM process to perform shock strengthening of the molten pool, utilizing the shock wave effect generated by the ultrafast laser to eliminate internal defects and refine grains. However, due to the significant mechanical effect of the ultrafast laser shock wave, when the shock wave acts on the powder bed surface, it dissipates the loose powder around the laser spot, forming pit-like morphologies with diameters ranging from 3 mm to 10 mm on the powder layer surface. If the ultrafast laser and the forming laser are closely aligned to achieve semi-molten shock strengthening, the shock wave dissipating the powder will lead to powder loss in the subsequent forming laser irradiation area, resulting in no powder to melt and preventing normal forming.
[0004] Therefore, it is difficult to achieve in-situ impact strengthening of semi-molten materials by ultrafast lasers while ensuring normal forming in existing technologies. Summary of the Invention
[0005] This invention provides a dual-laser composite forming method, applied to additive manufacturing equipment, comprising: S1: Control the sintering laser beam to irradiate the powder in the pre-forming area, so that the powder generates sintering neck bonding force in a non-melting state; S2: Control the forming laser beam to irradiate the pre-forming area, so that the powder in the pre-forming area forms a molten pool; S3: When the molten pool is in a semi-molten state, control the shock strengthening laser beam to irradiate the molten pool, wherein the shock strengthening laser beam is an ultrafast laser beam; The sintering laser beam acts on the pre-forming region before the forming laser beam, and the impact strengthening laser beam acts on the molten pool after the forming laser beam. The bonding force of the sintering neck is greater than the dispersing force of the shock wave of the impact strengthening laser beam on the powder.
[0006] Preferably, before controlling the sintering laser beam to irradiate the powder in the pre-forming area, the method further includes: expanding the initial laser beam to obtain the sintering laser beam; the magnification of the beam expansion process is in the range of 2 to 20 times, the diameter of the initial laser beam is 5 mm, and the diameter of the sintering laser beam is in the range of 10 mm to 100 mm.
[0007] More preferably, the spot diameter of the sintering laser beam is larger than the spot diameter of the forming laser beam, and the power of the sintering laser beam is less than the power of the forming laser beam.
[0008] More preferably, the power range of the sintering laser beam is 50W to 200W, the power range of the forming laser beam is 200W to 1000W, the peak power density range of the shock strengthening laser beam is 109W / cm2 to 1012W / cm2, and the pulse width range of the shock strengthening laser beam is 10fs to 100ps.
[0009] More preferably, the light spots of the sintering laser beam, the light spots of the forming laser beam, and the light spots of the impact strengthening laser beam are collinearly arranged on the plane where the preforming region is located, and the first distance between the center of the light spot of the sintering laser beam and the center of the light spot of the forming laser beam is equal to the second distance between the center of the light spot of the forming laser beam and the center of the light spot of the impact strengthening laser beam.
[0010] More preferably, the sintering laser beam spot, the forming laser beam spot, and the impact strengthening laser beam spot are arranged sequentially on the same scanning path, and the sintering laser beam spot, the forming laser beam spot, and the impact strengthening laser beam spot move synchronously along the scanning path. The first distance between the center of the sintering laser beam spot and the center of the forming laser beam spot remains unchanged during the synchronous movement, and the second distance between the center of the forming laser beam spot and the center of the impact strengthening laser beam spot remains unchanged during the synchronous movement.
[0011] Further preferably, the sintering neck bonding force consists of solid-state sintering neck force, van der Waals force, electrostatic force, and mechanical interlocking force; the solid-state sintering neck force is directly proportional to the product of particle diameter and material surface energy, and directly proportional to the square of the ratio of sintering neck radius to particle radius; the van der Waals force is directly proportional to the product of Hamaker constant and particle diameter, and inversely proportional to the particle surface spacing; the electrostatic force is directly proportional to the product of the charge of the first particle and the charge of the second particle, and inversely proportional to the square of the center-to-center spacing between the first particle and the second particle.
[0012] More preferably, the solid-state sintering neck force, the van der Waals force, and the electrostatic force are calculated using the following formulas: The formula for calculating the solid-state sintering neck force is as follows: Where D is the particle diameter, σ is the surface energy of the material, x is the sintering neck radius, and a is the particle radius; The formula for calculating the van der Waals force is as follows: Where A is the Hamaker constant and h0 is the particle surface spacing; The formula for calculating the electrostatic force is: Where q1 is the charge of the first particle, q2 is the charge of the second particle, r is the center-to-center distance between the first particle and the second particle, and ε0 is the vacuum permittivity.
[0013] More preferably, the lower limit of the temperature of the semi-molten state is the solidus temperature of the powder, and the upper limit of the temperature of the semi-molten state is the liquidus temperature of the powder.
[0014] More preferably, the scanning speed of the sintering laser beam, the scanning speed of the forming laser beam, and the scanning speed of the impact strengthening laser beam are equal.
[0015] Technical effects: This invention incorporates a sintering laser beam to pre-sinter loose powder in a non-molten state before the forming laser acts on the pre-forming area. This creates a sintering neck bond between powder particles, transforming the powder from a loose state into a sintered state with a certain impact resistance. This sintering neck bond is designed to be greater than the dispersing force of the impact-strengthening laser beam's shock wave on the powder. Therefore, when the shock wave generated by the subsequent impact-strengthening laser beam acts on the sintered powder, the powder will not be blown apart, avoiding the problem in existing technologies where the powder is blown apart, resulting in no powder available for the forming laser to melt. The impact-strengthening laser beam can perform impact strengthening on the material when the molten pool is in a semi-molten state. In the semi-molten state, the material has good plasticity and low deformation resistance. The shock wave can effectively act on the interior of the material, eliminating defects such as pores and cracks and refining the grains, thereby achieving continuous processing of forming and strengthening simultaneously. The preheating effect of the sintering laser on the powder changes the powder heating process from extremely rapid heating to gradient heating, reducing the accumulation of thermal stress in the material. At the same time, the sintering laser also has a preheating effect on the previous forming layer, which can alleviate the stress concentration caused by the rapid cooling of the previous forming layer, so that the entire forming and stress control process forms a closed loop, reducing post-processing steps. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the steps of the dual-laser composite forming method of the present invention.
[0017] Figure 2 This is a schematic diagram of the equipment system architecture used in the dual-laser composite forming method of the present invention. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0019] This invention provides a dual-laser composite forming method. The equipment includes a first laser for generating a sintering laser beam, a second laser for generating a forming laser beam, a third laser for generating an impact strengthening laser beam, an optical path system for guiding the three laser beams to the processing plane, a galvanometer system or scanning galvanometer system for controlling the scanning path of the laser beams, and a forming platform for supporting the powder bed. The three laser beams act on the pre-forming area in a predetermined spatial arrangement and sequentially on the same processing position in a temporal order. The sintering laser beam irradiates the pre-forming area before the forming laser beam, and the impact strengthening laser beam irradiates the molten pool after the forming laser beam.
[0020] Regarding the control of the sintering laser beam, the sintering laser beam is controlled to irradiate the powder within the pre-forming area, causing the powder to generate sintering neck bonding forces in a non-melting state. The sintering laser beam is generated by a first laser and processed by a beam expanding system to form a laser beam with a large spot diameter. The power of the sintering laser beam is set below the threshold power that would melt the powder; its function is to raise the surface temperature of the powder particles to the sintering temperature using the thermal diffusion effect without causing a melting phase transition in the powder. The spot diameter of the sintering laser beam is set to be larger than that of the forming laser beam to cover the pre-forming area and achieve uniform sintering. At the sintering temperature, the atoms on the surface of the powder particles acquire sufficient activation energy, and atoms on the surfaces of adjacent particles diffuse and migrate to each other, forming sintering necks at the particle contact interfaces. The formation of the sintering necks generates solid-phase sintering neck forces between the originally loose powder particles. Simultaneously, van der Waals forces, electrostatic forces, and mechanical interlocking forces also exist between the particles; the sum of these forces constitutes the sintering neck bonding force. After sintering, the powder transforms from a loosely packed state into a sintered state with integrity and impact resistance. The bonding force of the sintered neck is set to be greater than the dispersing force of the shock wave of the shock strengthening laser beam on the powder, so that the powder will not be blown away by the shock wave during the subsequent shock strengthening process.
[0021] Regarding the control of the forming laser beam, the forming laser beam is controlled to irradiate the pre-forming area, causing the powder within the pre-forming area to form a molten pool. The forming laser beam is generated by a second laser and has a small spot diameter and high power. The power of the forming laser beam is set to a value sufficient to rapidly heat the powder above its melting point and form a stable molten pool. When the forming laser beam irradiates the pre-forming area that has already undergone sintering, the powder is already in a sintered state rather than a loose state, resulting in higher thermal conductivity between powder particles. Furthermore, the powder particles are less prone to spattering under the influence of laser energy. Therefore, the forming laser can more effectively input energy into the powder, causing it to rapidly heat up and melt to form a molten pool. After the molten pool is formed, its temperature begins to decrease after the forming laser beam stops irradiating it.
[0022] Regarding the control of the shock-enhanced laser beam, when the molten pool is in a semi-molten state, the shock-enhanced laser beam is controlled to irradiate the molten pool. The shock-enhanced laser beam is an ultrafast laser beam, generated by a third laser, with a pulse width in the femtosecond to picosecond range and an extremely high peak power density. When the temperature of the molten pool drops to the semi-molten temperature range between the solidus and liquidus temperatures, the shock-enhanced laser beam is controlled to irradiate the molten pool. When the ultrafast laser irradiates the surface of the semi-molten pool, energy is deposited on the material surface layer in a very short time, causing the surface material to instantly vaporize and ionize to form a high-density plasma. The plasma expands rapidly, generating a shock wave that propagates into the material's interior. When this shock wave acts on the semi-molten material, because the material is in a solid-liquid coexistence state, it has low deformation resistance and good plasticity. The shock wave can effectively propagate into the material's interior, causing plastic deformation, closing internal pores and cracks, and simultaneously breaking columnar crystals or dendrites into fine equiaxed crystals. Because the sintering laser pre-sintersects the powder, a sintering neck bonding force has been formed between the powder particles. This bonding force is greater than the dispersing force of the shock wave from the shock-enhanced laser beam on the powder. Therefore, when the shock wave acts on the sintered powder, it will not break the powder apart, and the powder in the pre-formed area remains intact.
[0023] Regarding the beam expansion process, before the sintering laser beam irradiates the powder within the pre-forming area, the initial laser beam is expanded to obtain the sintering laser beam. The beam expansion system consists of beam expanders, which employ Galilean or Keplerian optical structures, composed of a combination of negative and positive lenses. After passing through the beam expanders, the initial laser beam diameter is magnified according to the beam expansion ratio. The beam expansion ratio is set to 2 to 20 times, with the initial laser beam diameter being 5 mm, and the expanded sintering laser beam diameter reaching 10 mm to 100 mm. The large spot diameter of the sintering laser beam allows it to cover a larger pre-forming area, improving the efficiency of the sintering process. Simultaneously, it results in a lower energy density for the sintering laser, which is beneficial for achieving uniform sintering of the powder in a non-melting state, avoiding localized melting of the powder due to excessively high energy density.
[0024] Regarding the parameter configuration of the sintering laser beam and the forming laser beam, the spot diameter of the sintering laser beam is set to be larger than that of the forming laser beam, while the power of the sintering laser beam is set to be lower than that of the forming laser beam. After beam expansion, the spot diameter of the sintering laser beam is significantly enlarged, while the spot diameter of the forming laser beam remains relatively small. The large spot diameter of the sintering laser beam, combined with its lower power, ensures that the powder only reaches the sintering temperature without melting when the sintering laser acts on it. The small spot diameter of the forming laser beam, combined with its higher power, ensures that the forming laser can rapidly heat the powder above its melting point and form a molten pool. Through this differentiated configuration of spot diameter and power, the sintering laser beam and the forming laser beam perform two different functions—sintering and melting / forming—in the same processing process, respectively, without interference. The large spot size of the sintering laser beam provides a preheating effect on the pre-forming area, helping to reduce the temperature gradient and thermal stress in subsequent forming processes.
[0025] Regarding the specific parameter ranges of the three laser beams, the power range of the sintering laser beam is 50W to 200W, the power range of the forming laser beam is 200W to 1000W, and the peak power density range of the impact strengthening laser beam is... to The pulse width of the shock-enhancing laser beam ranges from 10 fs to 100 ps. The power of the sintering laser beam is set between 50 W and 200 W. This power range, combined with a large spot diameter, ensures that the energy density of the sintering laser is sufficient to raise the surface temperature of the powder particles to the sintering temperature but not enough to melt the powder. The power of the forming laser beam is set between 200 W and 1000 W. This power range, combined with a small spot diameter, ensures that the energy density of the forming laser is sufficient to rapidly heat the powder above its melting point and form a stable molten pool. The peak power density of the shock-enhancing laser beam is set... to The pulse width is set between 10 fs and 100 ps. This parameter range ensures that the shock-enhanced laser beam generates a high-intensity shock wave in a very short time while having minimal thermal impact on the material. Under such high peak power density and such short pulse width conditions, when the shock-enhanced laser beam interacts with the material, the energy deposition time is much shorter than the heat diffusion time. Heat does not have enough time to diffuse into the material, so no heat-affected zone is generated.
[0026] Regarding the spatial arrangement of the three laser beams, the beams of the sintering laser beam, the forming laser beam, and the impact strengthening laser beam are collinearly arranged on the plane of the pre-forming area. The first distance between the center of the sintering laser beam and the center of the forming laser beam is equal to the second distance between the center of the forming laser beam and the center of the impact strengthening laser beam. The optical path system of the three laser beams is configured to form three collinearly arranged beams on the processing plane. Collinear arrangement means that the centers of the three beams are located on the same straight line. The distance between the center of the sintering laser beam and the center of the forming laser beam is defined as the first distance, and the distance between the center of the forming laser beam and the center of the impact strengthening laser beam is defined as the second distance. The first distance is equal to the second distance. This equidistant collinear arrangement ensures that when the three laser beams move synchronously along the scanning path, any position on the processing plane sequentially undergoes the sintering process of the sintering laser, the melting and forming process of the forming laser, and the impact strengthening process of the impact strengthening laser, with the time interval between each processing step remaining constant. The equidistant arrangement ensures the uniform distribution of the three steps of sintering, forming and impact strengthening in time and space, which is conducive to obtaining consistent processing quality.
[0027] Regarding the synchronous movement of the three laser beams, the spots of the sintering laser beam, the forming laser beam, and the impact strengthening laser beam are arranged sequentially along the same scanning path. These beams move synchronously along the scanning path. The first distance between the center of the sintering laser beam spot and the center of the forming laser beam spot remains constant during the synchronous movement, as does the second distance between the center of the forming laser beam spot and the center of the impact strengthening laser beam spot. The three laser beam spots are arranged sequentially along the scanning path on the processing plane, i.e., along the scanning direction, they are the sintering laser spot, the forming laser spot, and the impact strengthening laser spot. During scanning, the three spots move synchronously along the scanning path at the same speed, and the relative positions between any two spots remain constant. The first distance between the center of the sintering laser beam spot and the center of the forming laser beam spot remains constant during the movement, as does the second distance between the center of the forming laser beam spot and the center of the impact strengthening laser beam spot. The synchronous movement method ensures that any position on the processing plane is treated by the sintering laser, followed by the forming laser after a fixed time interval, and then by the impact strengthening laser after another fixed time interval. The fixed time interval is beneficial for controlling the timing of the impact strengthening laser irradiation on the molten pool in a semi-molten state, because the time required for the molten pool temperature to drop to the semi-molten temperature range at that position after the forming laser stops irradiating is fixed. By setting appropriate spacing and scanning speed, it is possible to precisely control the molten pool to be in a semi-molten state when the impact strengthening laser acts on it.
[0028] Regarding the composition of the sintering neck bonding force, it consists of solid-state sintering neck force, van der Waals force, electrostatic force, and mechanical interlocking force. The solid-state sintering neck force originates from the mutual diffusion and migration of atoms on the surface of adjacent particles at the contact interface during sintering. After a sintering neck forms at the particle contact interface, the atomic bonding at the sintering neck generates a force that pulls the particles together. The solid-state sintering neck force is directly proportional to the product of the particle diameter and the material surface energy, and also directly proportional to the square of the ratio of the sintering neck radius to the particle radius. Van der Waals force is the attractive force between particles due to intermolecular dispersion forces, inductive forces, and orientation forces. It is directly proportional to the product of the Hamaker constant and the particle diameter, and inversely proportional to the inter-particle distance. Electrostatic force is the Coulomb force between particles due to their respective electrostatic charges. It is directly proportional to the product of the charges of the first and second particles, and inversely proportional to the square of the center-to-center distance between the first and second particles. The mechanical interlocking force originates from the mechanical interlocking between the micro-rough structures on the particle surface. The four forces together constitute the sintering neck bonding force, which enables the sintered powder to resist external impacts.
[0029] Regarding the calculation formulas for the three forces, the formula for calculating the solid-state sintering neck force is as follows: ; Where D is the particle diameter. For the surface energy of the material, For the sintering neck radius, The particle radius is given. The particle diameter D is measured in meters (length units) and represents the size of the powder particles. The surface energy of the material... The dimension of is energy divided by area, with units of joules per square meter. It reflects the extra energy possessed by atoms on the material's surface relative to those inside, and is a crucial physical parameter determining the magnitude of the sintering driving force. Sintering neck radius The dimension is the meter, representing the lateral dimension of the neck structure formed by atomic diffusion at the interface between adjacent particles. Particle radius The dimension is the meter, representing the radius of the powder particles. Sintering neck radius. With particle radius The ratio of these two values is a dimensionless parameter, and the square of this ratio is also dimensionless. The particle diameter D and the material surface energy... The product of these two forces has dimensions in Joules per meter (Newtons), consistent with the dimension of force. This proportional relationship indicates that, under otherwise constant conditions, the larger the particle diameter, the greater the solid-state sintering neck force; the higher the material surface energy, the greater the solid-state sintering neck force; and the greater the ratio of the sintering neck radius to the particle radius, the greater the solid-state sintering neck force. The solid-state sintering neck force reaches its maximum value when the sintering neck radius approaches the particle radius. In actual sintering processes, the sintering neck radius gradually increases with increasing sintering time and temperature, and the solid-state sintering neck force also increases accordingly. The theoretical basis for this proportional relationship is the double-sphere model in solid-state sintering theory. This model is based on the kinetic analysis of neck growth in two adjacent spherical particles of equal diameter during sintering. By analyzing the relationship between the atomic diffusion flux on the particle surface and the neck curvature radius, a quantitative relationship between the solid-state sintering neck force and particle geometric parameters and material properties is derived. This model has been widely accepted in the field of sintering theory.
[0030] The formula for calculating van der Waals force is: ; Where A is the Hamaker constant, The distance between particle surfaces is denoted as A. The Hamaker constant A is dimensionless, expressed in joules (the unit of energy), and its typical value is usually found in the range of 1000-1000 Å. to The magnitude reflects the combined influence of a material's polarization properties on intermolecular forces. The dimension of particle diameter D is meter (length unit). The interparticle surface spacing... The dimension of is the meter, a unit of length, in closely contacting powder particles. Typically, the spacing is taken at the molecular scale, approximately 0.2 nm to 0.4 nm. The product of the Hamaker constant A and the particle diameter D, divided by the particle surface spacing, is used. The dimension of force, Newton, is then obtained, and dividing by 12 yields a constant coefficient. This formula shows that van der Waals forces are directly proportional to particle diameter and inversely proportional to the inter-particle spacing; the closer the inter-particle spacing, the stronger the van der Waals force. Van der Waals forces are the macroscopic manifestation of intermolecular forces at the particle scale. Their physical origin lies in the interaction of instantaneous dipole moments caused by electron cloud fluctuations in atoms or molecules, including three components: orientation force, induction force, and dispersion force, with dispersion force usually dominating. The Hamaker constant is a key parameter characterizing the strength of this interaction, and its value depends on the dielectric and optical properties of the material. In the initial stage of powder sintering, when the inter-particle spacing decreases to the nanoscale, van der Waals forces play an important role in particle adhesion and aggregation, and are one of the important contributing factors to the formation of powder agglomerates and the maintenance of sintering neck bonding forces.
[0031] The formula for calculating electrostatic force is: ; in, The charge of the first particle. The charge of the second particle. The distance between the centers of the first and second particles is denoted as . The vacuum permittivity. The value is 8.854 × 10 -12 The farad per meter is a fundamental physical constant in a vacuum. and These are the charges of the two particles, in coulombs. The distance between the center of the particles is denoted by the unit of length, meter. is the coulomb constant, with a value of 8.988 × 10⁻⁶. 9 The electrostatic force is expressed in Newton-square meters per square coulomb. This formula shows that the electrostatic force is directly proportional to the product of the charges of the two particles and inversely proportional to the square of the distance between their centers. When two particles carry the same charge, the electrostatic force is repulsive; when two particles carry opposite charges, the electrostatic force is attractive. In the actual process of powder sintering, powder particles usually carry static charges caused by triboelectric charging or surface states, thus creating electrostatic forces between particles. Friction between powder particles and components such as pipe walls and scrapers during conveying and spreading causes charge accumulation on the particle surface. Differences in the work function of different materials also lead to contact charging, resulting in different particles carrying static charges of different polarities and quantities. The electrostatic forces generated by these static charges have a significant impact on the interaction forces between powder particles and need to be considered when calculating the bonding force of the sintering neck.
[0032] The three formulas above quantitatively describe the mathematical relationship between three types of interaction forces and powder particle parameters from a physical mechanism perspective. The proportional relationship of the solid-state sintering neck force is based on the double-sphere model in solid-state sintering theory. This model establishes the relationship between the sintering neck force and particle size, material surface energy, and neck geometric parameters by analyzing the kinetic mechanism of neck growth between two adjacent particles during sintering. This relationship, starting from the physical basis of atomic diffusion and surface energy reduction, reveals the law of evolution of the solid-state sintering neck force during the sintering process. The calculation formula for van der Waals force is based on the Hamaker theory of intermolecular forces. This theory obtains a quantitative relationship between the interaction force between two macroscopic particles and particle size and spacing by integrating the Lennard-Jones potential energy between a single atom or molecule over the particle volume. This theory has been widely applied in colloid science and powder technology. The calculation formula for electrostatic force is the standard form of Coulomb's law, a fundamental law of electrostatics, describing the quantitative relationship between the force between two point charges in a vacuum and the amount of charge and distance. The combination of these three formulas constitutes a quantitative description system of the sintering neck bonding force, providing a theoretical basis for the analysis and control of the sintering neck bonding force. In practical applications, by selecting powder materials with appropriate particle diameter and surface energy, controlling sintering process parameters to adjust the sintering neck radius, and controlling the charge state of the powder, the magnitude of the sintering neck bonding force can be adjusted to meet the requirement of being greater than the shock wave dispersing force.
[0033] Regarding the temperature range of the semi-molten state, the lower limit of the semi-molten state is the solidus temperature of the powder, and the upper limit is the liquidus temperature of the powder. For alloy materials, the melting process is not completed at a single temperature point, but gradually within a temperature range. The solidus temperature refers to the temperature at which the alloy begins to melt; below this temperature, the alloy is completely solid. The liquidus temperature refers to the temperature at which the alloy completely melts; above this temperature, the alloy is completely liquid. Between the solidus and liquidus temperatures, the alloy is in a semi-molten state where solid and liquid phases coexist. When the molten pool temperature is within the semi-molten temperature range, both solid grains and liquid phases exist in the material. The liquid phase between the solid grains acts as a lubricant, giving the material lower deformation resistance and better plasticity. When a shock wave is applied in this state, the shock wave can be effectively transmitted to the interior of the material, causing plastic deformation and breakage of the solid grains. At the same time, the liquid phase can fill the micropores created after grain breakage, achieving defect elimination and grain refinement. If a shock wave is applied when the molten pool temperature is above the liquidus temperature (i.e., completely liquid), the molten pool will spatter and its morphology will be damaged under the shock wave, making effective impact strengthening impossible. If a shock wave is applied after the molten pool temperature has completely solidified (below the solidus temperature), the material's resistance to deformation is high, and the shock wave is unlikely to induce sufficient plastic deformation, resulting in a very limited strengthening effect. Controlling the timing of the impact strengthening laser beam so that the molten pool temperature is between the solidus and liquidus temperatures when it impacts the molten pool is a key condition for achieving effective impact strengthening.
[0034] Regarding the scanning speeds of the three laser beams, the scanning speeds of the sintering laser beam, the forming laser beam, and the impact strengthening laser beam are all equal. The scanning speeds of the three laser beams are set to equal values. When the three laser beams move synchronously along the same scanning path at the same speed, any position on the processing plane sequentially undergoes the three processing steps of sintering, forming, and impact strengthening, with the time interval between each step remaining constant. If the scanning speeds of the three laser beams are not equal, the relative positions between the three spots will change over time, resulting in inconsistent time intervals between processing steps and making it impossible to precisely control the temperature state of the molten pool when the impact strengthening laser acts on it. By setting the scanning speeds of the three laser beams to be equal, combined with an equally spaced, collinear spatial arrangement, it can be ensured that every position on the processing plane undergoes the exact same processing sequence, thereby obtaining uniform and consistent processing quality. The specific value of the scanning speed is determined comprehensively based on factors such as the thermophysical parameters of the powder material, laser power, and spot diameter to ensure that the sintering laser has sufficient time to complete sintering, the forming laser has sufficient time to form a stable molten pool, and the impact strengthening laser acts on the molten pool when it is in a semi-molten state.
[0035] Taking one specific embodiment as an example, the method of the present invention is used to perform laser additive manufacturing on 316L stainless steel powder. The powder particle diameter D is... Material surface energy 1.8J / m 2 The initial laser beam diameter was 5mm, and after 10x beam expansion, the sintering laser beam diameter was 50mm. The sintering laser beam power was set to 100W, the forming laser beam power was set to 400W, and the peak power density of the impact strengthening laser beam was set to 10. 11 W / cm 2 The pulse width is set to 100 fs. The sintering laser beam first irradiates the pre-forming area at a scanning speed of 100 mm / s, causing the powder to generate sintering neck bonding force in a non-molten state. Subsequently, the forming laser beam irradiates the same pre-forming area at the same scanning speed of 100 mm / s, causing the powder to form a molten pool. When the molten pool temperature drops to the semi-melting temperature range between the solidus and liquidus temperatures, the impact strengthening laser beam irradiates the molten pool at the same scanning speed of 100 mm / s, performing impact strengthening on the semi-molten material. In this embodiment, the formula for calculating the solid-state sintering neck force is: , When the sintering neck radius When it is 10μm, x / a = 10 / 15 ≈ 0.667, (x / a 2 )≈0.444, =30×10 -6 ×1.8=5.4×10 -5 N, Solid-state sintering neck force and 5.4×10 -5 ×0.444≈2.4×10 -5 It is directly proportional to N.
[0036] The formula for calculating van der Waals force is: , The Hamaker constant A is taken as 2.5 × 10⁻⁶. -19 J, Take 0.3nm = 3 × 10 -10 m, =2.5×10 -19 ×30×10 -6 =7.5×10 -24 , =12×3×10 -10 =3.6×10 -9 m, F van =7.5×10 -24 / 3.6×10-9 ≈2.08×10 -15 N.
[0037] The formula for calculating electrostatic force is: , Assume each particle carries 1.6 × 10 -18 The charge of C, Particle center spacing 30 μm = 3 × 10 -5 m, q1q2=2.56×10 -36 C 2 , =4π×8.854×10 -12 ≈1.113×10 -10 F / m, F electro =1 / (1.113×10 -10 ) × 2.56 × 10 -36 / (9×10) -10 ) ≈ 8.988 × 10 9 ×2.84×10 -27 ≈2.55×10 -17 N.
[0038] The three forces, along with the mechanical interlocking force, constitute the sintering neck bonding force. This bonding force is greater than the dispersing force of the shock wave from the impact-strengthened laser beam on the powder, therefore the shock wave will not dislodge the powder. Testing showed that the density of the 316L stainless steel sample formed using this method reached over 99.8%, internal porosity and cracks were eliminated, the grain structure changed from columnar to equiaxed, and the microhardness increased by approximately 20% compared to the un-impact-strengthened sample.
[0039] In another specific embodiment, the method of the present invention is used to perform laser additive manufacturing of Ti-6Al-4V titanium alloy powder. The powder particle diameter D is 45 μm, and the material surface energy... 2.1 J / m 2 The initial laser beam diameter was 5mm, and after 15x beam expansion, the sintering laser beam diameter was 75mm. The sintering laser beam power was set to 150W, the forming laser beam power was set to 600W, and the peak power density of the impact strengthening laser beam was set to... The pulse width is set to 50 fs. The sintering laser beam first irradiates the pre-forming area at a scanning speed of 60 mm / s, causing the powder to generate sintering neck bonding force in a non-molten state. Subsequently, the forming laser beam irradiates the same pre-forming area at the same scanning speed of 60 mm / s, causing the powder to form a molten pool. When the molten pool temperature drops to the semi-molten temperature range, the impact strengthening laser beam irradiates the molten pool at the same scanning speed of 60 mm / s, performing impact strengthening on the semi-molten material. In this embodiment, since the liquidus temperature of the Ti-6Al-4V alloy is approximately... The solidus temperature is approximately The semi-melting temperature range is to The molten pool from Cool to The required time was determined to be approximately [time value missing] through finite element thermal simulation. Therefore, the distance between the impact strengthening laser beam spot and the forming laser beam spot is set to... ,exist At the scanning speed, the time interval is This method ensures that the molten pool is in a semi-molten state when the impact-strengthening laser is applied. Testing showed that the Ti-6Al-4V sample formed using this method achieved a density of over 99.9%, and the grain size after impact strengthening decreased from the original size. Refine to The tensile strength was increased by about 25% compared to the unimpact-strengthened specimen.
[0040] In another specific embodiment, the method of the present invention is used to perform laser additive manufacturing of Inconel 625 nickel-based alloy powder. Powder particle diameter... for Material surface energy for The initial laser beam diameter is After being expanded 5 times, the diameter of the sintering laser beam is The sintering laser beam power is set to The power of the shaping laser beam is set to The peak power density of the shock-enhanced laser beam is set to Pulse width set to The sintering laser beam first... The scanning speed irradiates the pre-forming area, causing the powder to generate sintering neck bonding forces in a non-molten state. Subsequently, the forming laser beam operates at the same speed... The same pre-formed area is irradiated at the same scanning speed, causing the powder to form a molten pool. As the molten pool temperature decreases to the semi-melting temperature range, the shock-enhanced laser beam operates at the same... The molten pool is irradiated with a scanning velocity to perform impact strengthening on the semi-molten material. In this embodiment, the large spot diameter of the sintering laser beam... This allows for the coverage of a larger preformed area in a single scan, improving forming efficiency. Due to the high high-temperature strength and good thermal stability of Inconel 625 alloy, the impact strengthening effect is particularly significant, resulting in a creep rupture life of the formed parts that is approximately 30% longer than that of un-impact-strengthened samples.
[0041] The above embodiments are merely illustrative. In practical applications, the powder material is not limited to 316L stainless steel, Ti-6Al-4V titanium alloy, and Inconel 625 nickel-based alloy; it can also be aluminum alloy, cobalt-chromium alloy, copper alloy, or other metal powder materials. The powder particle diameter is not limited to... to Alternatively, it can be selected based on specific process requirements. to Any value within the range. The power of the sintering laser beam is not limited to... to It can also be selected based on the powder material and scanning speed. to Any value within the range. The power of the shaped laser beam is not limited to... to It can also be selected based on powder material, layer thickness, and scanning speed. to Any value within the range. The peak power density of the shock-enhanced laser beam is not limited to... to Alternatively, it can be selected based on material properties and reinforcement requirements. to Any value within the range. The pulse width of the shock-enhanced laser beam is not limited to... to Alternatively, it can be selected based on the material's thermal diffusivity and the required strengthening effect. to Any value within the range. The scanning speed of the three laser beams is not limited to... to Alternatively, it can be any suitable value determined based on the thermal properties of the powder material, laser power, and spot diameter. The spacing between the three laser spots is determined according to the scanning speed and the molten pool cooling rate to ensure that the molten pool is in a semi-molten state when the shock-enhancing laser acts on it. The beam expansion ratio is determined according to the required sintering spot diameter. Doubled The selection should be within a range of [number] times. The selection and adjustment of the above parameters are all within the conventional technical capabilities of those skilled in the art; appropriate parameter values can be determined based on specific process conditions and material properties without any creative effort.
[0042] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments that can be applied to other fields. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A dual-laser composite forming method, applied to additive manufacturing equipment, characterized in that, include: S1: Control the sintering laser beam to irradiate the powder in the pre-forming area, so that the powder generates sintering neck bonding force in a non-melting state; S2: Control the forming laser beam to irradiate the pre-forming area, so that the powder in the pre-forming area forms a molten pool; S3: When the molten pool is in a semi-molten state, control the shock strengthening laser beam to irradiate the molten pool, wherein the shock strengthening laser beam is an ultrafast laser beam; The sintering laser beam acts on the pre-forming region before the forming laser beam, and the impact strengthening laser beam acts on the molten pool after the forming laser beam. The bonding force of the sintering neck is greater than the dispersing force of the shock wave of the impact strengthening laser beam on the powder.
2. The dual-laser composite forming method according to claim 1, characterized in that, Before controlling the sintering laser beam to irradiate the powder in the pre-forming area, the method further includes: expanding the initial laser beam to obtain the sintering laser beam; the magnification of the beam expansion process is in the range of 2 to 20 times, the diameter of the initial laser beam is 5 mm, and the diameter of the sintering laser beam is in the range of 10 mm to 100 mm.
3. The dual-laser composite forming method according to claim 1, characterized in that, The spot diameter of the sintering laser beam is larger than that of the forming laser beam, and the power of the sintering laser beam is less than that of the forming laser beam.
4. The dual-laser composite forming method according to claim 1, characterized in that, The power range of the sintering laser beam is 50W to 200W, the power range of the forming laser beam is 200W to 1000W, the peak power density range of the shock strengthening laser beam is 109W / cm2 to 1012W / cm2, and the pulse width range of the shock strengthening laser beam is 10fs to 100ps.
5. The dual-laser composite forming method according to claim 1, characterized in that, The sintering laser beam spot, the forming laser beam spot, and the impact strengthening laser beam spot are collinearly arranged on the plane of the pre-forming area. The first distance between the center of the sintering laser beam spot and the center of the forming laser beam spot is equal to the second distance between the center of the forming laser beam spot and the center of the impact strengthening laser beam spot.
6. The dual-laser composite forming method according to claim 5, characterized in that, The sintering laser beam spot, the forming laser beam spot, and the impact strengthening laser beam spot are arranged sequentially on the same scanning path. The sintering laser beam spot, the forming laser beam spot, and the impact strengthening laser beam spot move synchronously along the scanning path. The first distance between the center of the sintering laser beam spot and the center of the forming laser beam spot remains unchanged during the synchronous movement, and the second distance between the center of the forming laser beam spot and the center of the impact strengthening laser beam spot remains unchanged during the synchronous movement.
7. The dual-laser composite forming method according to claim 1, characterized in that, The sintering neck bonding force consists of solid-state sintering neck force, van der Waals force, electrostatic force, and mechanical interlocking force; the solid-state sintering neck force is directly proportional to the product of particle diameter and material surface energy, and directly proportional to the square of the ratio of sintering neck radius to particle radius; the van der Waals force is directly proportional to the product of Hamaker constant and particle diameter, and inversely proportional to the particle surface spacing; the electrostatic force is directly proportional to the product of the charge of the first particle and the charge of the second particle, and inversely proportional to the square of the center-to-center spacing between the first particle and the second particle.
8. The dual-laser composite forming method according to claim 7, characterized in that, The solid-state sintering neck force, the van der Waals force, and the electrostatic force are calculated using the following formulas: The formula for calculating the solid-state sintering neck force is as follows: Where D is the particle diameter, σ is the surface energy of the material, x is the sintering neck radius, and a is the particle radius; The formula for calculating the van der Waals force is as follows: Where A is the Hamaker constant and h0 is the particle surface spacing; The formula for calculating the electrostatic force is: Where q1 is the charge of the first particle, q2 is the charge of the second particle, r is the center-to-center distance between the first particle and the second particle, and ε0 is the vacuum permittivity.
9. The method according to claim 1, characterized in that, The lower limit of the temperature of the semi-molten state is the solidus temperature of the powder, and the upper limit of the temperature of the semi-molten state is the liquidus temperature of the powder.
10. The method according to claim 1, characterized in that, The scanning speeds of the sintering laser beam, the forming laser beam, and the impact strengthening laser beam are all equal.
